The Potential of Salvinia molesta as a Copper Phytoremediation Agent based on Gene Expression Analysis - Astuti, Sutan Nur Chamida Tri; Solihah, Jumailatus; Aisah, Siti (Universitas Ahmad Dahlan, 2023)
This research explores the rapid environmental impact of the batik industry, particularly concerning batik waste pollution, especially from the heavy metal copper (Cu). Untreated batik waste can have adverse effects on the environment. The study highlights the potential of the water fern plant (Salvinia molesta) as a heavy metal phytoremediator, specifically for Cu, by activating phytochelatin synthase. The research aims to determine the most effective waste concentration for Cu absorption by water ferns, measure the reduction in Cu levels after phytoremediation treatment, evaluate post-phytoremediation water quality, and observe PCS gene expression in the roots and leaves of water ferns. A static method is employed with variations in waste concentrations. Data analysis utilizes one-way ANOVA for Cu level reduction and changes in water quality. The results indicate that the most effective wastewater concentration for absorbing heavy metal copper (Cu) using water fern (Salvinia molesta) is 2%. The highest reduction in heavy metal copper (Cu) concentration after phytoremediation treatment with water fern (Salvinia molesta) is 41.48%. Water quality post-phytoremediation treatment using water fern (Salvinia molesta) at all concentrations exhibits improvement with an increase in dissolved oxygen (DO) levels. The expression of the phytochelatin synthase (PCS) gene in the leaves and roots of water fern (Salvinia molesta) confirms the role of the PCS gene in binding heavy metal copper (Cu) to the plant's vacuole.